The State of Soil Chemical Fertility in Pineapple Agrotourism Land, Bolaang Mongondow Regency - Adinda Putri Sudjono Wasir; Zetly E. Tamod; Tommy D. Sondakh (Jurnal Agroekoteknologi Terapan, 2022)
Soil is a natural resource mostly from the surface of the planet earth that is capable of growing plants and has properties as a result of the influence of climate and living organisms that act on the parent material in certain relief conditions. This shows that an area can have different soil properties. This study aims to Based on the results of research that has been carried out in the pineapple agro-tourism area of Bolaang Mongondow Regency, it shows that the nutrient content of the land is low - very low, while the soil pH on the land is neutral. Thus, efforts to increase nutrient fertility at locations in the area can be done through fertilization of both organic and anorganic fertilizers. determine the chemical fertility of the soil (pH, KTK, N, P, K, Ca and C-organic). Key words: Agrotourism Land, Soil Fertility Abstrak Tanah adalah sumber daya alam yang sebagian besar berasal dari permukaan planet bumi yang mampu menumbuhkan tanaman dan memiliki sifat sebagai akibat pengaruh iklim dan organisme hidup yang bertindak atas bahan induk dalam kondisi relief tertentu. Hal ini menunjukkan bahwa suatu daerah dapat memiliki sifat tanah yang berbeda-beda. Penelitian ini bertujuan Berdasarkan hasil penelitian yang telah dilakukan di kawasan agrowisata nanas Kabupaten Bolaang Mongondow menunjukkan bahwa kandungan unsur hara tanah rendah – sangat rendah, sedangkan pH tanah pada tanah tersebut adalah netral. Dengan demikian, upaya peningkatan kesuburan hara pada lokasi-lokasi di kawasan dapat dilakukan melalui pemupukan baik pupuk organik maupun anorganik. menentukan kesuburan kimia tanah (pH, KTK, N, P, K, Ca dan C-organik). Kata Kunci : Lahan Agrowisata, Kesuburan Tanah